Soil Potassium Fractions as Influenced by Integrated Fertilizer Application Based on Soil Test Crop Response under Maize-Wheat Cropping Systems in Acid Alfisol - Kurbah, Ibajanai; Dixit, S. P. (International Journal of Economic Plants, 2019)
Field experiments were conducted during 2014–15 to 2015–16 at the Experimental Farm of Department of Soil Science, CSK Himachal Pradesh Krishi Vishvavidyalaya, Palampur, HP as a part of long-term fertilizer experiment initiated in kharif, 2007 in a maize-wheat sequence. The experiment consisted of eight treatments viz., (1) control; (2) general recommended dose; (3) soil test based; (4) farmers’ practice; (5) target yield of 25 and 30 for rabi and kharif, respectively without FYM; (6) target yield of 25 and 30 for rabi and kharif, respectively with FYM @ 5 t ha-1 (7) target yield of 35 and 40 q ha-1 for rabi and kharif, respectively without FYM; (8) target yield of 35 and 40 q ha-1 for rabi and kharif, respectively with FYM @ 5 t ha-1) which were replicated thrice in a randomized block design. The fertilizer adjustment equations were developed based on target yield concept and accordingly nutrient doses were calculated. The results revealed that soil available K was significantly increased in both the target yields with IPNS over general recommended dose and soil test based treatments. The different forms of potassium i.e. water soluble K, exchangeable K and non- exchangeable K were highest under STCR (IPNS) treatment for target yield of 35 q ha-1. The status of non-exchangeable potassium was significantly inferior in unfertilized plots in comparisons to all other treatments. Regression analysis showed that exchangeable K was the most important variable contributing about 94% in the total variation in available- K.